ACCOUNTING AND REPORTING IN THE ENTERPRISE MANAGEMENT SYSTEM - Halushchak, I.Ye.; Lutsiv , N.L. (The actual problems of regional economy development, 2021)
The article is directed at the study of accounting and reporting in the enterprise management system. The purpose of the article is to study accounting and reporting in the enterprise management system. During the writing of the article, the main general scientific research methods were used, such as: analysis, synthesis, induction and deduction. Accounting as the basis of the information system of enterprise management is discovered. Disclosure of the periodization of the development of accounting as one of the components of management. The main aim of the information system is formed. The structure of accounting is shown. The most important objects of information support of enterprise management from the point of view of realization of accounting tasks are given. The legal basis for regulation, organization and maintenance of accounting and preparation of financial statements in Ukraine is defined. The role of state regulation in accounting is determined. Indicator of financial reporting in the system of information support, justification and decision-making. The connection of financial statements with the main classical functions of management is revealed. The concept of accounting policy of enterprises is given. The components of the accounting policy for expenses, income and financial results are presented. The main characteristics of accounting are given. The general set of all information at the enterprise is classified. It is investigated that in the conditions of the strengthened competition the question concerning accounting and the reporting in the organization, any form of ownership and a kind of activity, became one of the most important stages of process of administration at the enterprise. The importance of this phase is that the basis of success and efficiency is not only accounting and management, but also analysis and control, which play no less important role in management resolve. Accounting, like any component of business requires regulation by the state and recognition at the interstate level, and the system of accounting for expenses, income and financial results of the enterprise in modern conditions can not fully exist without a proper regulatory framework.